Another Side of the Antidiuretic Hormone, Vasopressin: Its Role in Stress Regulation - Subodh Kumar Jain1,2*, Dóra Zelena1 (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Vasopressin (AVP) is an ancient molecule of the salt-water homeostasis. On the other hand, in the brain AVP can be found in many regions, where it has a prominent role in the regulation of stress and stress related diseases, too. During acute stress AVP regulates the adrenocorticotropin secretion in a time and stressor specific manner. Its role seems to be especially critical during the perinatal period. Despite earlier theories, during chronic stress the role of AVP has never been highlighted. AVP seems to be also responsible for our mood. Its high level is accompanied by higher level of anxiety and depression. Pharmacological intervention of the AVP secretion could influence not only the salt-water homeostasis, but might have strong impact on our stress state and behaviour.